2011
DOI: 10.3171/2011.3.focus1165
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of intracranial cavernous malformations

Abstract: Literature reports on the natural history of cerebral cavernous malformations (CMs) are numerous, with considerable variability in lesion epidemiology, hemorrhage rates, and risk factors for hemorrhage. In this review, the authors performed a meta-analysis of 11 natural history studies. The overall male-to-female ratio was 1:1, and the mean age at presentation was 30.6 years. Overall, 37% of patients presented with seizures, 36% with hemorrhage, 23% with headaches, 22% with focal neurological deficits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(262 citation statements)
references
References 31 publications
12
236
2
3
Order By: Relevance
“…13,70 Among the general population, the reported prevalence of CNS cavernous malformations is 0.4%-0.6%. 16,25,31,48,52,56 These lesions most often occupy the intracranial (mainly supratentorial) compartment. 10,16,25,33,52,66 By contrast, spinal cord cavernous malformations are very rare entities, accounting for 5%-12% of intraspinal vascular malformations.…”
mentioning
confidence: 99%
“…13,70 Among the general population, the reported prevalence of CNS cavernous malformations is 0.4%-0.6%. 16,25,31,48,52,56 These lesions most often occupy the intracranial (mainly supratentorial) compartment. 10,16,25,33,52,66 By contrast, spinal cord cavernous malformations are very rare entities, accounting for 5%-12% of intraspinal vascular malformations.…”
mentioning
confidence: 99%
“…The frequently observed coexistence of CM indicates the existence of a form occurring between the stages of capillary and venous malformation. 8,11,12 This entity should be managed in time to avoid severe sequelae as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…12 The unique characteristics of the giant BCTs in our series add more support to this theory. 6,8,11 Small BCT and CM might be the two ends of the same pathological entity, with giant or large BCT as the bridging developmental stage. Moreover, it has been suggested that either BCT or CM could develop as a consequence of dynamic change in the blood flow and then develop into the other type of lesion (i.e., CM or BCT).…”
Section: Diagnosis Of Bctsmentioning
confidence: 99%
“…Cavernous malformations are common cerebrovascular abnormalities, affecting 0.4-0.8% of the general population 13,14,15 . Pathologically, CCM are defined by clusters of dilated capillary cavities, in back-to-back disposition, lined by a single layer of endothelium, lacking smooth muscle and no intervening brain parenchyma 16 ( Figure 1).…”
Section: Familial Cerebral Cavernous Malformations (Fccm)mentioning
confidence: 99%